Gastrointestinal microbiota and metabolites responses to dietary cereal grains in an adult pig model - Feng, Ganyi; Deng, Menglong; Li, Rui; Hou, Gaifeng; Ouyang, Qing; Jiang, Xianji; Liu, Xiaojie; Tang, Hui; Chen, Fengming; Pu, Shihua; Wan, Dan; Yin, Yulong (Frontiers in Microbiology, 2024)
Corn (C), wheat (W), and paddy rice (PR) are important energy sources and are commonly used in feed production for swine. This study mainly focuses on the variation and regularities of microbiota and metabolites in the gastrointestinal tract (GIT) of pigs in response to C, W, and PR. A total of 18 pigs were allotted into three dietary groups with six replicated pigs and received diets containing C, W, or PR as the sole energy source, respectively. The results showed that digestive parts significantly affected the diversity of microbial communities. Cereal grain sources significantly influenced the β-diversity of microbial communities in the colon and rectum. Campylobacterota and Proteobacteria are mainly distributed in the duodenum, Lactobacillus in the jejunum, and Bacteroidota in the colon and rectum. The W diet increased the Bacteroidota, Spirochaetota, and Prevotellaceae_NK3B31_group abundances and showed the highest concentrations of all short-chain fatty acids (SCFAs) in the hindgut. Fibrobacterota, Bacteroidota, Spirochaetota, Prevotellaceae_NK3B31_group, Prevotella, and Treponema in the colon or rectum were positively correlated with acetate, propionate, butyrate, and total SCFAs. These findings suggested that aerobic bacteria and facultative anaerobes in the foregut will gradually be replaced by anaerobes in the hindgut. The W diet had the best fermentability and was beneficial to the colonization of microbial communities that mainly used carbohydrates. The hindgut flora of the PR diet group may be more balanced with fewer potential pathogenic bacteria. Many microbial communities have been identified to contribute positively to the SCFA production of the hindgut. Collectively, our study revealed the spatial variation regularities of GIT microbial communities in an adult pig model and provided new insights into GIT microbiota and responses of metabolites to cereal grain diets.